Solve for w 6=w/3+3

Math
6=w3+3
Rewrite the equation as w3+3=6.
w3+3=6
Move all terms not containing w to the right side of the equation.
Tap for more steps…
Subtract 3 from both sides of the equation.
w3=6-3
Subtract 3 from 6.
w3=3
w3=3
Multiply both sides of the equation by 3.
3⋅w3=3⋅3
Simplify both sides of the equation.
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Cancel the common factor.
3⋅w3=3⋅3
Rewrite the expression.
w=3⋅3
w=3⋅3
Multiply 3 by 3.
w=9
w=9
Solve for w 6=w/3+3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top